Adaptation and Validation of the Self Transcendence Inventory for Adults in the Argentine context - Simkin, Hugo (Pensando Psicología, 2019)
Introduction: In recent years self-transcendence has gained increasing interest within psychological literature. Currently, the Adult Self Transcendence Inventory (ASTI) is one of the main scales used in empirical research for measuring self transcendence.Objective: The present study aims to adapt and validate the scale to the Argentine context in a sample of 205 high school and university students in the Autonomous City of Buenos Aires.Method: A confirmatory factor analysis of the factor structure of the adapted Adult Self Transcendence Inventory was conducted to assess whether the scale's purported 2 factors emerged. The results generally supported the 2-factor model.
Keywords: adaptation; confirmatory factorial analysis; self transcendence; spirituality; validation